Faktor-Faktor Yang Mempengaruhi Akhlak Anak Putus Sekolah di Jorong Balai Cubadak Nagari Taram Kecamatan Harau Kabupaten Lima Puluh Kota - Putri, Mailian; Jasmienti, Jasmienti; Iswantir, Iswantir; Fauzan, Fauzan (Indonesian Research Journal on Education, 2023)
This research is motivated by the morals of school dropouts in various forms. The morals of these school dropouts are commendable and some have despicable characters, not all school dropouts have despicable morals, but there are also commendable ones. Out-of-school children certainly do not get a full education so dropouts have despicable morals such as: being dishonest, likes to lie, talk rudely, and are also easily influenced by the outside environment which makes dropout children like to steal otherpeople's things. The purpose of this study was to determine the factors that influence the morals of school dropouts in Jorong Balai Cubadak Nagari Taram, Harau District, Lima Puluh Kota Regency so that the morals of dropouts have noble character. This type of research is descriptive qualitative research. In collecting data, the writer uses observation, interview, and documentation techniques. Meanwhile, to analyze it, the researcher took several steps, namely data reduction, presenting data, and drawingconclusions. Based on the results of the research that has been carried out, it can be concluded that the factors that influence the morals of school dropouts in Jorong Balai Cubadak are instinct, innate or inherited, environment, habits, will, and education. A bad environment will affect the morals of school dropouts to behave despicably and if the innate or inherited parents have good morals, the morals of dropout children will have noble character.